2004
DOI: 10.1093/carcin/bgh165
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of arachidonic acid metabolism by curcumin and related  -diketone derivatives: effects on cytosolic phospholipase A2, cyclooxygenases and 5-lipoxygenase

Abstract: Aberrant arachidonic acid metabolism is involved in the inflammatory and carcinogenic processes. In this study, we investigated the effects of curcumin, a naturally occurring chemopreventive agent, and related beta-diketone derivatives on the release of arachidonic acid and its metabolites in the murine macrophage RAW264.7 cells and in HT-29 human colon cancer cells. We also examined their effects on the catalytic activities and protein levels of related enzymes: cytosolic phospholipase A(2) (cPLA(2)), cycloox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
251
1
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(266 citation statements)
references
References 36 publications
7
251
1
7
Order By: Relevance
“…Ginsenoside Rb1 isolated from red ginseng significantly decreased histamine and leukotriene production in a dosedependent manner during mast cell activation [21] as well as lipopolysaccharide-induced proinflammatory cytokine production [43]. Recently, dietary pigment, curcumin appears to block H pylori-induced NF-κB activation, IL-8 gene expression, the cell scattering response [35], and modulate AA metabolism including PLA 2 , COX, and 5-LOX [44]. In a similar way, we found that red ginseng can also regulate H pylori-induced NF-κB activation and subsequent expression of IL-8 in gastric AGS cells associated with 5-LOX regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Ginsenoside Rb1 isolated from red ginseng significantly decreased histamine and leukotriene production in a dosedependent manner during mast cell activation [21] as well as lipopolysaccharide-induced proinflammatory cytokine production [43]. Recently, dietary pigment, curcumin appears to block H pylori-induced NF-κB activation, IL-8 gene expression, the cell scattering response [35], and modulate AA metabolism including PLA 2 , COX, and 5-LOX [44]. In a similar way, we found that red ginseng can also regulate H pylori-induced NF-κB activation and subsequent expression of IL-8 in gastric AGS cells associated with 5-LOX regulation.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds may be regarded as potent and direct 5-LO inhibitors. Similarly, the well-recognized curcumin 52 from Curcuma longa L. [39], [129] and the structurally related gingerols 53 from Zingiber officnialis Roscoe [115], [116] proved to inhibit 5-LO in cell-based and cell-free assays with IC 50 < 1 mM. Interestingly, compared to the prenylated hyperforin 48, the structurally related polyphenols such as erychristagallin 46 [130], or kuraridin 47 [105] possessing lipophilic prenyl residues (that seemingly enhance the potency of flavonoids) are significantly less effective with IC 50 values > 20 mM.…”
Section: Inhibitors Of 5-lo Product Synthesis From Plant Originmentioning
confidence: 99%
“…Interestingly, 5-LO and cPLA 2 share structural (C2 domain) and regulatory properties [activated by Ca 2+ and by phosphorylation by members of the mitogen-activated protein kinase (MAPK) family] [31], [34]. Indeed, many studies revealed that natural compounds (e. g., flavonoids and other polyphenols) leading to suppression of LT formation also act as PLA 2 inhibitors preventing AA release [35], [36], [37], [38], [39], [40]. The anti-inflammatory sesterterpenoid manoalide, for instance, is an irreversible inhibitor of PLA 2 enzymes by covalently modifying lysine residues [41].…”
mentioning
confidence: 99%
“…Likewise, the LOX pathway produces leukotrienes which, like PGs, are potent causal pain agents. One polyphenol compound, curcumin, inhibited COX-dependent arachidonic acid metabolism by 23%, displayed a strongest inhibitory effect on the peroxidase activity of ovine COX-1 (IC 50 ∼50 μM), and significantly decreased induced COX-2 expression (20 μM), although the underlying mechanism remains poorly understood (68,69). Very low concentrations of salicylic acid found in the blood following ingestion of aspirin (10-30 mg doses) have been shown to suppress COX-2 transcription and are thought to explain epidemiological observations which link aspirin use with reduced risk for colon cancer (70).…”
Section: Inflammation-sincementioning
confidence: 99%